Keragaman Sistem Pengisian Jabatan Kepala Daerah Sebagai Manifestasi Demokrasi: Perbandingan Antara Australia, Belgia, dan Hungaria (JIMLY LEGAL YUSTISIA JOURNAL, 2026)
The manifestation of democracy in one country is certainly not the same as in another. Democracy is the process of creating and maintaining a civil society by respecting, striving for, and realizing the values to which a society aspires. Indonesia is undergoing a dynamic process in the implementation of its democracy, and what has been done should be evaluated in the direction of a more ideal democracy. In the practice of local government administration, both in Indonesia and a number of other countries such as Australia, Belgium and Hungary, there is a wide variety of systems for filling regional head positions. However, until now there is no standard measure to determine that a system of filling regional head positions by direct election would be more democratic than an indirect election system. A system certainly has its own advantages and disadvantages. Therefore, comparing the success of the system for filling regional head positions in many countries can be a good lesson for filling the constitutional gap in the 1945 Constitution of the Republic of Indonesia.